(untitled) (Journal of Information Technology and Digital World, 2023)
This article is all about the ChatGPT. As AI is one of the emerging technologies in the current era. The application of AI “ChatGPT” is mainly focused in this study. This study concentrates on the technology behind ChatGPT, its advantages, limitations, and discussions on current trending applications of AI called ChatGPT. Considering AI technology, the article will provide the glimpse of the learning technologies, Generative Pre-Trained Transformer (Particularly GPT-3 and GPT-2), and also discuss how many education institutions are using AI. By method of data collection some conclusions could be drawn on ChatGPT users and user interaction experiences. In addition, what is ChatGPT, the purpose of ChatGPT, why it has gained extensive popularity and attention, methods of training ChatGPT along with Large Language Models, how ChatGPT makes use of GPT-3 and RLHF (Reinforcement Learning form Human Feedback), advantages and limitations of ChatGPT are also comprehended.